Implementation of audiovisual resources as an educational validation strategy (2018)
This paper is the outcome of a quasi-experimental research, whose objective was to validate an educational strategy aimed at implementing audiovisual learning resources in educational institutions. Its theoretical foundation was configured through two variables: educational practices (dependent variable), and audiovisual resources (independent variable). With a control group model comprised of 11th grade students from the Institución Educativa Camilo Torres of Mocarí (Montería, Colombia), it was possible to identify the most frequent learning needs of secondary education students, to classify the audiovisual educational resources available to the teachers, and to model, implement and validate an educational strategy by assembling three audiovisual products, three radio programs, and a blog.